Effect of Oxytocin Augmentation on Neonatal Bilirubin Levels : A Case Control Study - Jitendra Shukla; Shubhra Buch; Piyusha Chandrayan (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction - Hyperbilirubinemia is a commonly encountered problem in both term as well as preterminfants and is a source of concern to neonatologists.Aim- to determine the relationship between the usage of oxytocin during labour and the developmentof neonatal hyperbilirubinemia.Methodology- a case controlled study was conducted. 50 patients were given intravenous oxytocinfor the augmentation of their labour and 50 patients delivered spontaneously without the usage ofoxytocin during their labour. The neonates born to both these categories of patients were studied fortheir bilirubin levels of day 2 of life.Results- hyperbilirubinemia developed in 34% of the neonates whose mothers were given oxytocin foraugmentation of labour and hyperbilirubinemia developed in only 14% of the neonates whose mothersdelivered spontaneously without the usage of oxytocin.Conclusion- A positive relationship between the usage of oxytocin during labour and development ofneonatal hyperbilirubinemia has been established.